Environmental protection : key prerequisite for sustainable tourism on the Mediterranean - Jovičić, Dobrica (Array, 2008)
Abstract: The Mediterranean is grown up as one of the most developed tourist regions on the Earth, but development of mass tourism brought to the big saturation of space, causing environmental problems. As a consequence, today the Mediterranean is faced with a great challenge: how to preserve natural and cultural values as a basis for tourism industry and, in the same time, to keep high reputation on the globalized tourist market. In this work are analyzed the environmental effects of tourism and problems aggravating the concept of the sustainable development. There are also shown the key measures, that can enable development of tourism on a sustainable basis. Particular attention is dedicated to institutional and organizational factors having a crucial role in defining guidelines related to protection and sustainable usage of the Mediterranean Sea with its coastal area